2010
DOI: 10.1080/19315260.2010.504251
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Variation Among Faba Bean Landraces and Cultivars

Abstract: Landraces of crops can contain phenotypic and genotypic variability that can be exploited so that new lines can be developed. The phenotypic and genotypic variability among 11 Jordanian faba bean (Vicia faba L.) landraces and five imported cultivars were studied. Yield and 12 yield components and yield-related traits were evaluated at two locations. Analysis indicated significant variability among germplasm for all characters and among locations for 10 characters, in which final plant height, pods/plant, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Genomic DNA was extracted from fresh leaves of the 20 accessions using the cetyltrimethylammonium bromide method as described by Torres et al. (1993) with minor modifications (Abu‐Amer et al. 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA was extracted from fresh leaves of the 20 accessions using the cetyltrimethylammonium bromide method as described by Torres et al. (1993) with minor modifications (Abu‐Amer et al. 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Because of limited availability of SSR markers in faba bean (Abu‐Amer et al. 2011, Gong et al 2011), the objectives of this study were to develop new faba bean EST‐SSR markers, to validate their ability to detect polymorphism among 13 different faba bean genotypes and to investigate their transferability across seven related Vicia spp.…”
mentioning
confidence: 99%
“…A similar analysis with AFLP markers emphasized the separation of the Chinese local landraces of faba bean from the rest (Zong et al 2009), with a wide variability within the spring-sown ones . Similar studies using SSR markers in the local landraces of faba bean from Jordan (Abu-Amer et al 2010) and isozymes for those from Ethiopia (Serradilla et al 1993) also showed a local separation within the regions of Near East and North Africa. On the other hand, a wide variability was assessed among the local landraces in one country, such as Greece , Egypt (Mustafa 2007) or Ethiopia (Keneni et al 2005), opening a possibility that the geographic factors does not have to play a pivotal role on a lower level.…”
Section: Faba Beanmentioning
confidence: 67%